Energy consumption, weather variability, and gender in the Philippines: A discrete/continuous approach - Connie Bayudan-Dacuycuy (Philippine Institute for Development Studies (PIDS), 2017)
Using a discrete/continuous modeling approach, this paper analyzes energy use and consumption in the Philippines within the context of weather variability and gender. Consistent with energy stacking strategy where households use a combination of traditional and modern energy sources, this paper finds that households use multiple energy sources in different weather fluctuation scenarios. It also finds that weather variability has the highest effects on the electricity consumption of balanced and female-majority households that are female headed and in rural areas. Several policies are suggested.
Keywords: Q4; Q49; D12; 330; Discrete/continuous approach; weather variability; gender; energy choice; energy consumption